PREPARATION OF BUNDLING STRATEGY AND IMPROVEMENT OF BRAND AWARENESS WITH INSTAGRAM PROMOTION STRATEGY AT FOJA COFFEE MSME - Ilham Bayu Bramasto (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2023)
AbstractIn Indonesia, micro, small and medium enterprises (MSMEs) are one of the drivers of the economy. The important role of the existence of MSMEs in Indonesia is significant role in the process of national economic development in Indonesia. This research was conducted through a business coaching process, in which the coach helped the coachee (MSME owner) and a series of structured interviews and observations with the MSME owner Foja Coffee, an MSME engaged in Coffee Business typical in the area of East Jakarta and West Java. This study aims to analyze problems related to preparing a financial statement, and to increase brand awareness by implementing appropriate promotional strategies at Foja Coffee MSME. This research uses Business Model Canvas Analysis methodology, Marketing Mix Analysis, STP Analysis, PESTEL Analysis, Porter's Five Forces Analysis, GAP Analysis, SWOT Analysis, and Pareto Analysis. The application of in-store advertising solutions and social media marketing SOPs when MSME Foja Coffee conducts promotions to welcome the fasting month of Ramadan. The SOPs for Social Media Marketing in question is to set target posts or impressions every certain time frame and funding in the marketing effort. Delays in Foja Coffee's MSME business processes due to different opening times cause owners to not get representative customer data like in previous months or years. An alternative step that the owner can take is to take advantage of Instagram social media that he already has as a promotional medium at this time. Its function can be developed as an online sales channel during this Ramadan so that Foja Coffee MSMEs can continue to operate.Keywords: Business Coaching, Financial Statements, Brand Awareness, MSME, Promotion Strategies